Avalia????o da express??o de neuropept??deo Y em hipocampo de ratos com epilepsia induzida pela pilocarpina - Silva, Marcelo de Paula Alves da (2010)
Neuropeptide Y was discovered in the decade of 80 and consisting of 36 amino acids. The aim of this study was to analyze the neuropeptide Y (NPY) RNAm expression in hippocampi of epileptics rats. Male Wistar rats were submitted to the pilocarpine model of epilepsy. Hippocampi were removed 6h (acute phase), 12h (late acute), 5d (silent) and 60d (chronic) after status epilepticus (SE) onset, and from animals that received pilocarpine but did not develop SE (partial group). Hippocampi collected were used to specify RNAm expression using Real time PCR. Neuropeptide Y RNAm expression increased in the partial group (1.67??0.22) and in the silent phase (1.45??0.29) when compared to control group (0.36??0.12). Results suggest that neuropeptide Y (as anticonvulsant) might act in protective mechanisms occurred during epileptic phenomena. This neuroactive peptide could be involved in hippocampal neuroprotection in epilepsy.